Strategic Formulation for Sustainable Campus Development: A SWOT-TOWS Analysis of Sebelas Maret University, Indonesia - Muzzazinah; Murtanti Jani Rahayu; Suryanto; Yanti Sulistyana; Feni Andriani (Magister Program of Material Science, Graduate School of Universitas Sriwijaya, 2026)
Higher education institutions must implement appropriate evaluation and strategy determination to support their role in establishing a Sustainable Campus. This study aims to (1) evaluate the implementation of the sustainable campus program at Universitas Sebelas Maret (UNS), (2) analyze the dominance of internal (IFAS) and external (EFAS) factors at UNS, and (3) formulate strategies that UNS should implement to strengthen its sustainable campus initiatives-the implementation evaluation utilized data from the UNS GreenMetric report. The factor dominance analysis employed IFAS and EFAS, while the strategy formulation used SWOT-TOWS analysis. The findings indicate that UNS has stagnant scores in the Water (WR) and Transportation (TR) indicators. Furthermore, UNS’s strengths lie in its open space availability and sustainable academic programs, though this advantage is hindered by limited budget allocation for toxic waste management. Based on the analysis, the recommended course of action for UNS is the Strengths-Opportunities (SO) strategy. The implementation of this SO strategy is necessary for UNS to advance its role as a sustainable campus successfully. This study implies that the integration of sustainability performance evaluation using UI GreenMetric data with IFAS, EFAS, and SWOT-TOWS analysis provides a structured basis for identifying dominant strategic conditions and formulating strength-oriented strategies to improve sustainable campus implementation at Universitas Sebelas Maret. The study implies that Universitas Sebelas Maret should utilize sustainability assessment results as strategic inputs rather than merely as reporting tools, enabling more targeted interventions in critical areas such as water and transportation management. These findings may further contribute to the development of management strategies derived from SWOT and TOWS analyses in other universities across Indonesia.